Legal Pluralism in the Colonial Era: The Influence of Economic Globalization on the Elimination of Poenale Sanctie and Customary Law - Azwar, Tengku Keizerina Devi; Baxadirovna, Bazarova Dildora (Faculty of Law, Universitas Pattimura, 2025)
Introduction: From the late nineteenth to the early twentieth century, the expansion of large-scale plantations driven by global capital created a dual legal order in which colonial law was positioned as the dominant system, while customary law became subordinated. The central issues explored are how economic globalization shaped the configuration of legal pluralism and what factors contributed to the abolition of the poenale sanctie within the colonial legal system.Purposes of the Research: The purpose of this research is to analyze the dynamics between colonial and customary law in the context of global economic change and to investigate the underlying causes of the abolition of the poenale sanctie.Methods of the Research: This is normative legal research employing a conceptual approach. Data were drawn from primary legal sources, including colonial regulations and official archives; secondary legal sources, such as academic literature; and tertiary supporting materials. The data were then analyzed using a qualitative-descriptive method.Results of the Research: The findings reveal that the abolition of the poenale sanctie was influenced by both international and internal factors. External pressures included global public opinion and the rise of ethical politics, while internal drivers involved labor resistance, humanitarian advocacy, economic efficiency considerations, and the evolution of modern criminal law. The novelty of this research lies in its analysis of the implications of the abolition of the poenale sanctie for the status of customary law in East Sumatra. The study demonstrates that despite reforms within the colonial legal system, customary law did not gain significant recognition but remained marginalized. Hence, this research contributes to the discourse on colonial legal pluralism by highlighting the tension between economic globalization, colonial governance, and the persistence of customary law.